A New Unsaturated Aliphatic Anhydride from Aspergillus candidus T1219W1, an Endophytic Fungus, from Pittosporum mannii Hook f. - Gaëlle Talle Juidzou; Elodie Gisèle Mouafo Anoumedem; Denis Kehdinga Sema; Virginie Flaure Tsague Tankeu; Peron Bosco Leutcha; Larissa Yetendje Chimi; Jean Paul Dzoyem; Simeon Kouam Fogue; Norbert Sewald; M. Iqbal Choudhary; Alain Meli Lannang (Journal of Chemistry)
A new unsaturated aliphatic anhydride derivative (Z)-(12Z)-heptadec-12-enoic-2′-hydroxypropanoic anhydride (1) and ten known compounds, three flavonoids (2–4), two terphenyllins (5-6), four triterpenoids (7-8, 10-11), and one n-fatty acid (9), were isolated from the EtOAc extract of Aspergillus candidus T1219W1, an endophytic fungus, inhabiting Pittosporum mannii. All the isolated compounds were characterized using 1D- and 2D-NMR and HR-EI experiments together with the reported literature. p-terphenyls are suggested to be the chemophenetic marker of the genus Aspergillus. The ethyl acetate crude extract as well as some isolated compounds of A. candidus was assayed for antibiofilm activity, anti-inflammatory (ROS) activity, and cytotoxicity on brine shrimps and the MTT (3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide) cytotoxicity assay on 3T3 cell lines. The tested sample showed good antibiofilm activity with the lowest MBEC50 obtained at 64 μg/mL. Compounds showed low anti-inflammatory activity even at high concentration (250 μg·mL−1 with an IC50 of 59.6 ± 0.1 μg·mL−1) with moderate cytotoxicity on brine shrimps at high concentration (1000 μg·mL−1, with 46.67% mortality). However, no cytotoxic activity was observed against 3T3 cell lines.